Transgenerational inheritance of susceptibility to diabetes-induced male subfertility - Pavlinkova, Gabriela; Margaryan, Hasmik; Zatecka, Eva; Valaskova, Eliska; Elzeinova, Fatima; Kubatova, Alena; Bohuslavova, Romana; Peknicova, Jana (Scientific reports, 2017)
Male infertility is a worldwide problem associated with genetic background, environmental factors, and diseases. One of the suspected contributing factors to male infertility is diabetes mellitus. We investigated the molecular and morphological changes in sperms and testicular tissue of diabetic males. The study was performed in streptozotocin-induced type 1 diabetes mouse model. Diabetes decreased sperm concentration and viability and increased sperm apoptosis. Changes in protamine 1/protamine 2 ratio indicated reduced sperm quality. The testicular tissue of diabetic males showed significant tissue damage, disruption of meiotic progression, and changes in the expression of genes encoding proteins important for spermiogenesis. Paternal diabetes altered sperm quality and expression pattern in the testes in offspring of two subsequent generations. Our study revealed that paternal diabetes increased susceptibility to infertility in offspring through gametic alternations. Our data also provide a mechanistic basis for transgenerational inheritance of diabetes-associated pathologies since protamines may be involved in epigenetic regulations.
Keywords: zvířata; Biomarkers; Female; Phenotype; biologické markery; meióza; myši; fenotyp; testis; genetická predispozice k nemoci; protaminy; Infertility, Male; Animals; typy dědičnosti; mužská infertilita; diabetes mellitus 1. typu; Meiosis; Mice; spermie; mužské pohlaví; Genetic Predisposition to Disease; Diabetes Mellitus, Type 1; Testis; Male; ženské pohlaví; Inheritance Patterns; Spermatogenesis; spermatogeneze; Spermatozoa; Protamines